History of a failure: attempts to create a national Truth and Reconciliation Commission in Bosnia and Herzegovina, 1997–2006 - Dragovic-Soso, Jasna (International journal of transitional justice, 2016)
Several initiatives to create a national Truth and Reconciliation Commission (TRC) for Bosnia and Herzegovina were launched between 1997 and 2006, but none came to fruition. This article explains the rationale behind the pursuit of a truth-telling mechanism alongside the International Criminal Tribunal for the former Yugoslavia (ICTY), as well as the resistance to such initiatives both internationally and domestically. It argues that, despite the considerable efforts of external actors to create a TRC for Bosnia, the project foundered for three principal reasons: political resistance, institutional rivalry between the ICTY and the TRC project, and the TRC project’s lack of legitimacy, notably among Bosnia’s victim associations. The history of the failed TRC project in Bosnia holds important lessons for ongoing truth-seeking attempts in the region and beyond, and highlights problems that arise in postconflict societies with a high level of international involvement.